Respectful and safe childbirth - who recommendations and practice in Serbia - Sekulić Nada M. (Temida)
The paper examines the justification for using the term “obstetric violence” and emphasises the significance of recognising this type of gender-based violence. It further analyses practices in maternity wards in Serbia based on several previously conducted studies, comparing them with the current recommendations of the World Health Organisation (WHO) in this field. The WHO highlights the importance of a positive childbirth experience for both the mother and the child, emphasizing the active role of the mother and her natural potential in achieving a quality delivery. The paper presents comparative data, focusing particularly on the use of epidural anaesthesia as a recommended practice and the application of a group of interventions (episiotomy, induction, Kristeller manoeuvre) that are almost routinely performed in Serbian maternity wards but are not recommended as routine interventions by the WHO. The analysis of research findings conducted in Serbia points to the need for improving protocols and humane care related to childbirth, as well as the necessity of more comprehensive promotion of a childbirth model that ensures safety while respecting patients’ rights and dignity, including women’s specific reproductive rights.